On the Adsorption, by Activated Carbons, of Some Sparingly Soluble Organics from Aqueous Solutions - Hugi-Cleary, Deirdre; Slasli, Abdou; Stoeckli, Fritz (My University, 2005)
Activated carbons play an important role in the purification of air and of water. Whereas vapors are adsorbed by a micropore filling process, the removal of sparingly soluble species such as phenol and its derivatives is limited to the coating of the effective surface of the material. This reduces considerably the sorptive capacity of a given carbon, and a suitable description is needed to predict the corresponding equilibrium. It is shown that, in the case of phenol, its derivatives, and a few typical pollutants, the latter process can be described by an extension of the Dubinin-Radushkevich-Kaganer (DRK) equation. A major advantage of this approach is the possibility of calculating the adsorption equilibrium based on simple physicochemical properties of the adsorptives and on the structural characteristics of the activated carbon. It also appears that, by analogy with adsorption in the vapor phase, a scaling factor can be introduced for adsorption from solution.